ADOPSI PETANI TERHADAP TEKNOLOGI PENGELOLAAN TANAMAN TERPADU DI DESA JEMBAYAN TENGAH KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA (Farmers Adoption to Integrated Crop Management Technology in Jembayan Tengah Village Loa Kulu Subregency Kutai Kartanegara Regency) - MUHAMMAD ADITIA RIZKIE; NDAN IMANG (Universitas Mulawarman (University of Mulawarman), 2021)
Adoption of agricultural technology is one indicator of the success of extension activities. This study aimed to determine the level of adoption of wetland paddy farmers to Integrated Crop Management (ICM) technology from technical and non-technical aspects. This research was conducted from October to December 2019, in Jembayan Tengah Village, Loa Kulu Subregency, Kutai Kartanegara Regency. The sampling method used simple random sampling. The number of samples was 38 wetland paddy farmers. The data analysis was done by using descriptive method. The research results showed the level of adoption of wetland paddy farmers to ICM technology from the technical aspect in the high category with an average score of 120.29 and from the non-technical aspects in the high category with an average score of 58.47. In general, the adoption rate of wetland paddy farmers towards PPT technology is in the high category with an average score of 178.76.